2021
DOI: 10.1002/chem.202103585
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Anions and Secondary Coordination Sphere in Tuning Anisotropy in Dy(III) Air‐Stable D5h SIMs**

Abstract: Precise control of the crystal field and symmetry around the paramagnetic spin centre has recently facilitated the engineering of high‐temperature single‐ion magnets (SIMs), the smallest possible units for future spin‐based devices. In the present work, we report a series of air‐stable seven coordinate Dy(III) SIMs {[L2Dy(H2O)5][X]3⋅L2⋅n(H2O), n = 0, X = Cl (1), n=1, X = Br (2), I (3)} possessing pseudo‐D5h symmetry or pentagonal bipyramidal coordination geometry with high anisotropy energy barrier (Ueff) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…For 1 , the out-of-phase (χ M ″) susceptibility data under a zero dc field show well-defined maxima at temperatures up to 64 K (Figure a,b), indicating high-temperature slow magnetic relaxation with a high magnetization reversal barrier. The invariable positions of peaks in frequency dependence of χ M ″ and the “tails” phenomenon in temperature dependence of χ M ″ were observed below 10 K, due to the presence of fast quantum tunneling magnetization (QTM) at the zero dc field, which is commonly observed in lanthanide-based SMMs. The characteristic relaxation times (τ) were extracted from fitting the Cole–Cole plots to the generalized Debye model, which is presented in Figures c and S10. The α parameter found is in the range of 0–0.33 showing a wide distribution of relaxation times (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 1 , the out-of-phase (χ M ″) susceptibility data under a zero dc field show well-defined maxima at temperatures up to 64 K (Figure a,b), indicating high-temperature slow magnetic relaxation with a high magnetization reversal barrier. The invariable positions of peaks in frequency dependence of χ M ″ and the “tails” phenomenon in temperature dependence of χ M ″ were observed below 10 K, due to the presence of fast quantum tunneling magnetization (QTM) at the zero dc field, which is commonly observed in lanthanide-based SMMs. The characteristic relaxation times (τ) were extracted from fitting the Cole–Cole plots to the generalized Debye model, which is presented in Figures c and S10. The α parameter found is in the range of 0–0.33 showing a wide distribution of relaxation times (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…However, the synthesis of these linear Dy­(III) complexes faces great challenges. Alternatively, the complexes with axial symmetrical structures, such as square antiprism ( D 4 d ), trigonal bipyramid ( D 3 h ), octahedron ( D 4 h ), pentagonal bipyramid ( D 5 h ), , and hexagonal bipyramid ( D 6 h ), have been found to be very interesting regarding the enhancement of U eff and T B . For these geometries, one common feature is the disposition of two strong field ligands along the shortest axial bond combined with the weak equatorial ligands, which affords a very strong axial CF and generates a huge magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetization data revealed that, for isotropic Gd complexes 1 Gd , 3 Gd and 5 Gd at 2 K, the highest magnetization values of 13.88 and 13.83 Nβ at 7 T are slightly lower than the theoretical saturation value of 14 Nβ for two isolated Gd 3+ ions, while for Dy analogues, the magnetization values are far from a saturation of 20 Nβ for a dinuclear Dy system, indicating the presence of significant magnetic anisotropy and/or low-lying excited states in all systems. 26…”
Section: Resultsmentioning
confidence: 99%
“…These molecular magnets are the promised candidate for various technological applications such as high-density data storage devices, spintronics, quantum computation, qubit, etc. , The anisotropic energy barrier for magnetic relaxation through the Orbach process is mainly due to axial magnetic anisotropy. , Due to the unquenched orbital angular momentum and strong spin–orbit coupling, lanthanides have inherent large magnetic anisotropy and are suitable candidates to construct SMMs. To date, several mono- and multinuclear systems/complexes, including Ln-based coordination polymers have been reported, , of which dysprosium metallocene complexes, with high axial anisotropy have shown a higher performance. The under barrier magnetic relaxations such as quantum tunneling of magnetization (QTM), Raman, and direct processes suppress the high-performance of SMMs. The more effective QTM process reported in the lanthanide systems consists of the strong admixing of the ground ± mJ state with the low lying excited ± mJ states owing to the weak crystal field effect on the Ln III ion. However, the symmetry strategy around lanthanide geometry can help to minimize the QTM. ,,, As stated above, the insignificant separation of the excited states from the ground state can promote QTM, while the presence of QTM in high-performance SMMs, which consist of well-separated excited ± mJ levels, can be attributed to the vibronic coupling which in turn triggers the magnetic relaxation. , Not only the vibronic coupling but also the presence of other factors such as hydrogen bonding, size of the counterions, etc., are reported to trigger/promote the QTM by introducing the transverse component. ,, In this line of interest, we have isolated a series of novel 1D lanthanide (Dy ( 1 ‑Dy ), Gd ( 2 ‑Gd ), and La ( 3 ‑La )) coordination polymers by utilizing the mesityl derived benzimidazolium tricarboxylic acid H 3 L ligand system having three flexible carboxylate arms for coordination. The direct current (dc) and alternating current (ac) magnetic susceptibility data were recorded for 1 ‑Dy and 2 ‑Gd.…”
Section: Introductionmentioning
confidence: 99%